Pornography web sites classification using principle component analysis with neural network - Lee, Zhi Sam (2007)
Internet users have begun to protect themselves and their wards by using so-called web content filters, which allow access to legitimate content and block access to objectionable, illegal, and otherwise harmful content. Next to active filtering technologies, which use heuristics, machine learning and similar techniques from the area of text and image classification to analyze web pages, there is the complementary category of passive content filters, which rely on (mostly voluntary) content rating systems to classify web pages.